PENGARUH KECEPATAN PELAYANAN, FASILITAS, DAN KENYAMANAN TEMPAT TERHADAP KEPUASAN KONSUMEN DI RUMAH MAKAN NAN KANDUANG - Febriana Maharani; Muhammad Fadli Luran2 Fadli Luran; Samad Samad (Manajerial dan Bisnis Tanjungpinang, 2026)
Abstract: This study aims to analyze the effect of service speed, facility adequacy, and place comfort on customer satisfaction at Nan Kanduang Restaurant, Batam. This research is motivated by increasingly intense competition in the culinary industry, which requires business operators to pay attention to the overall consumer experience, not merely relying on food quality alone. A quantitative causal approach was applied involving 99 respondents selected through the Slovin formula with a 10% error rate and incidental sampling from a population of 6,890 customers during October–December 2025. Data were collected via Likert-scale questionnaires, supported by observation and interviews, then analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination with SPSS. The results prove that service speed, facilities, and place comfort—both partially and simultaneously—have a positive and significant effect on customer satisfaction, with an F-value of 146.536 exceeding the F-table of 2.70, significance of 0.000 < 0.05, and R² of 0.822, meaning 82.2% of the variation in customer satisfaction is explained by the three variables, while the remaining 17.8% is influenced by other factors outside this study.